PDE9 Inhibitor PF-04447943 Attenuates DSS-Induced Colitis by Suppressing Oxidative Stress, Inflammation, and Regulating T-Cell Polarization - Rana, Mohammad Nasiruddin; Lu, Jie; Xue, Enfu; Ruan, Jingjing; Liu, Yuting; Zhang, Lejun; Dhar, Rana; Li, Yajun; Hu, Zhengqiang; Zhou, Jie; Ma, Wangqian; Tang, Huifang (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a form of inflammatory bowel disease, which manifested as irritation or swelling and sores in the large intestine in a relapsing and remitting manner. In UC, cyclic guanosine monophosphate (cGMP) is evidenced to be compromised. Besides, we have found that mRNA expression of phosphodiesterase 9A (PDE9A) is predominant among all phosphodiesterase’s (PDEs) in dextran sulfate sodium (DSS)-induced colitis female mice model. Since, PDE9 have the highest affinity towards the cGMP, we have considered PDE9 inhibitor as potential candidate of treatment. PF-04447943(PF) is widely known as the PDE9A selective inhibitor, which is extensively studied in the cognitive function and sick cell disease. However, there is no study in the IBD model. Therefore, we used female C57BL/6 mice treated with 3% DSS alone or co-treated with PF or SASP for 7 days to study the body weight, colon length, and measured superoxide dismutase (SOD), malondialdehyde (MDA), and cGMP level, the number of goblet cell, as well as numbers of inflammatory mediators and pathways including nuclear factor kappa B (NF-kB), signal transducer and activator of transcription 3 (STAT3), and inflammasome activation. Besides, the number of dendritic cells (DC) and regulatory T cells (Treg cell) were assessed in the spleen, lymph node, and colon using flow cytometry. As results, DSS reduced the number of goblet cells, in agreement with decreased the colon length and body weight, which were attenuated by PF treatment. PF treatment also placated the DSS induced inflammation by suppressing oxidative stress, NF-kB, STAT3, and inflammasome activation, by upregulating nuclear factor erythroid 2–related factor 2 (Nrf-2) and its downstream proteins via extracellular signal-regulated kinase (ERK) phosphorylation. Importantly, PF reversed the imbalanced the Treg/Th17 cell, plausibly regulating the dendritic cells as well as orchestrating the Treg development process. In a nutshell, this study exhibited the protective effect of a PDE9A inhibitor in ulcerative colitis by suppressing oxidative stress and inflammation reverting the maintenance of Treg/ T helper 17 cell (Th17) cell balance, may open up a new avenue for PDE9A inhibitor.